2021
DOI: 10.1016/j.chest.2020.08.2056
|View full text |Cite
|
Sign up to set email alerts
|

Post-ICU COVID-19 Outcomes

Abstract: Patients critically ill with coronavirus disease 2019 (COVID-19) spend significant time on mechanical ventilation and have prolonged hospitalization duration. 1 Whether these patients have immediate pulmonary and neurocognitive recovery following discharge is unknown. Methods Patients were admitted to the University of Virginia (UVA) Medical Center ICU with COVID-19 and underwent follow-up at the UVA Post-COVID-19 ICU clinic approximately 6 weeks following discharge. Lung function and exercise capacity were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
59
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 8 publications
8
59
2
Order By: Relevance
“…To determine an optimal cutoff limit and nonspecific binding in the assay, samples from COVID-19 patients ( n = 51) and samples from allergic and nonallergic donors banked prior to the emergence of COVID-19 ( n = 109) were assayed using ImmunoCAPs conjugated with SARS-CoV-2 protein and also unconjugated “naked” streptavidin ImmunoCAPs. The COVID-19 samples were obtained from the 15 hospitalized patients described above, as well as 36 patients evaluated in an outpatient follow-up clinic following hospitalization for COVID-19 [ 18 ]. IgG binding to naked streptavidin ImmunoCAPs was observed at low levels in both COVID-19 and pre-CO­VID-19 samples (online suppl.…”
Section: Resultsmentioning
confidence: 99%
“…To determine an optimal cutoff limit and nonspecific binding in the assay, samples from COVID-19 patients ( n = 51) and samples from allergic and nonallergic donors banked prior to the emergence of COVID-19 ( n = 109) were assayed using ImmunoCAPs conjugated with SARS-CoV-2 protein and also unconjugated “naked” streptavidin ImmunoCAPs. The COVID-19 samples were obtained from the 15 hospitalized patients described above, as well as 36 patients evaluated in an outpatient follow-up clinic following hospitalization for COVID-19 [ 18 ]. IgG binding to naked streptavidin ImmunoCAPs was observed at low levels in both COVID-19 and pre-CO­VID-19 samples (online suppl.…”
Section: Resultsmentioning
confidence: 99%
“…These findings add to previous studies reporting a lower prevalence of pulmonary dysfunction in patients with COVID-19. However, these reports were based on less severely ill patients with COVID-19 who were not supported by invasive mechanical ventilation ( 4 ) or who were ventilated for a shorter duration ( 5 ). As such, our data represent the more severe spectrum of COVID-19 disease.…”
Section: Discussionmentioning
confidence: 99%
“…The included patients were overall younger than the general ICU-treated population [8, 23,24]; moreover, patients with PICS impairments tended to use systemic steroids or benzodiazepines, which are known factors for mental and physical PICS [25]. Additionally, long-term health effects across all severities have been recognized in numerous COVID-19 survivors [2,3]. Second, our patients were victims of a new and obscure disease and also a phenomenal pandemic.…”
Section: Mechanismsmentioning
confidence: 99%
“…Although there have been recent reports regarding long-term consequences, including fatigue, insomnia, and anxiety or depression, among COVID-19 survivors at or 6 months after acute infection, information regarding critically ill patients remains missing [2,5, 6]. Small-scale studies investigating ICU treated patients with COVID-19 have suggested that respiratory, mobility, and cognitive consequences are common at approximately a month after hospital discharge [3, 6]. However, PICS occurrence in COVID-19 survivors remains largely unclear.…”
mentioning
confidence: 99%